DEVELOPMENT AND RESEARCH OF THE NEW STEEL 75‘/25ГМФС FOR THE INSTRUMENT OF COLD FORMING - V. M. Fedulov (Литьë и металлургия)
The problems of improving tool life of cold deformation. Composition designed and studied mechanical properties of the new tool steel 75H5GMFS, by allowing the application of different types of heat treatment, including high-temperature tempering after casting, the use for the manufacture of cold-forming tool, for example, upon receipt of the housings of watches brass billets.